2003
DOI: 10.1097/00001721-200302000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of blood coagulation in severe liver disease using thromboelastography

Abstract: Thromboelastography evaluates the viscoelastic properties of blood coagulation. Using native blood, measurement must start soon after sampling. With normal coagulation, native and citrated blood values correlate well. No data exists from cirrhotic patients. We compared native and citrate thromboelastography parameters in 30 cirrhotic patients (20 Child-Pugh C class, two liver failure). Thromboelastography was performed within 4 min using native blood and after recalcification within 1-2 h of citrate storage. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Among these, only one study investigated severely ill patients. 10 In this study, no differences were observed when comparing fresh and citrate-stored blood samples.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Among these, only one study investigated severely ill patients. 10 In this study, no differences were observed when comparing fresh and citrate-stored blood samples.…”
Section: Discussionmentioning
confidence: 57%
“…There is some concern, however, that TEG results obtained from citrated blood samples may yield results different from those obtained from fresh, non citrated blood samples. [7][8][9][10] Another concern is that the storage time of citrated blood samples may influence TEG measures. [7][8][9]11 Consequently, to compare the results of TEG analysis, performed on non citrated blood, analyzed within five minutes of collection, with the values of citrated blood, stored, with and without use of activators, for one to three hours, we carried out this observational study on healthy volunteers.…”
Section: Reports Of Original Investigationsmentioning
confidence: 99%
“…35 Newer versions of the thromboelastogram (TEG) further offer automation and the ability to perform the test on citrated and recalcified blood for up to 3 hours after phlebotomy, thus greatly enhancing the practical utility of the test. 36 Key elements of the whole blood TEG include the reaction time (r) which reflects the quantity of available factors, clot formation time (k), the alpha angle (␣) reflecting the rate of clot formation and indirectly indicating fibrinogen levels, the maximal amplitude (ma) which is an indicator of platelet activity and finally a measure of clot lysis. Modifications of the primary assay, such as the addition of heparinase, make the test more robust but the dearth of clinical studies limit its application and endothelial function is not directly assessed in this assay.…”
Section: Conventional Tests Of Coagulation and Bleeding Risk In Livermentioning
confidence: 99%
“…For each patient, a native (without heparinase) and a heparinase I-modified TEG was performed. The time interval between the venepuncture and the beginning of TEG was based on the basis of previous data (36) showing that TEG results on native blood are comparable to those obtained from citrated blood in cirrhotic patients solely between a 1 h and 2 h interval after the blood sample has been obtained. The blood was then mixed with the activator in the cup by lowering the column three times and covered with mineral oil to eliminate the blood-air interface and prevent drying during analysis.…”
Section: Thromboelastography (Teg)mentioning
confidence: 99%